Fitting of the cumulative function for a distribution of statistic from the one-sample Anderson-Darling test - Tuluchenko, Halyna Yakivna (Bogolyubov Institute for Theoretical Physics, 2024)
У цих тезах показано, що кумулятивна функція A1(z) з одновибіркового тесту Андерсона-Дарлінга може бути апроксимована із задовільною точністю кумулятивною функцією, що належить до узагальненої родини кумулятивних функцій спеціального виду. In these abstarct, it is shown that the cumulative function A1(z) from the one-sample Anderson-Darling test can be fitted with satisfactory accuracy by a cumulative function belonging to a generalized family of cumulative functions of a special form.
Keywords: cumulative function; one-sample Anderson-Darling test; generalized distribution; інтегральна функція розподілу; одновибірковий тест Андерсона-Дарлінга; узагальнений розподіл